Chlamyda trachomatis y sus factores de riesgo como indicador de infecciones vaginales en trabajadoras sexuales de la provincia de Loja - Salazar Piedra, Anabel Stefanie (2015)
The Chlamydia trachomatis is a causal agent of sexually transmission very frequent to level of the world, the kinds more frequent of sexually transmitted diseases (ETS) produced for trachomatis are urogenital infections, in particular urethritis no gonococcal, pelvic inflammatory diseases, although it`s usually asymptomatic , the undiagnosed infection in the women can lead to acute salpingitis, with a high risk of ectopic pregnancy or tubal infertility; for that reasons we studied and analyzed the prevalence of Chlamydia trachomatis , the used of the preservatives and the relation between the two obtained data in the sex workers because it`s a group of high risk; realizing a study of transversal cut, descriptive, quantitative, in which we realized the analysis of blood sample through of the test Inmuno Comb Chlamydia trachomatis IgA and the application of a survey to determine the Condom use like a protection method against the sexual transmission infections (ITS); concluding that 42% are infected by Chlamydia trachomatis, the 4% don`t Condom use like protection method against the ITS, which is considered like predisposing factor to acquire the disease; then to do the relation between the two data we can demonstrate that isn`t a factor of acquire Chlamydia trachomatis the no Condom use; looking that it is a asymptomatic disease, must be to implement this test in the control of the mentioned population and try to awareness about the existence of the ITS and the factors of risk to acquire them. Clue words: Chlamydia trachomatis, infecciones vaginales, IgA.